1993
DOI: 10.1016/s0006-3495(93)81252-9
|View full text |Cite
|
Sign up to set email alerts
|

Actin binding to lipid-inserted alpha-actinin

Abstract: The interaction of alpha-actinin with lipid films and actin filaments was investigated. First alpha-actinin was incorporated in lipid films at the air/water interface. Injection of alpha-actinin into the subphase of a lipid monolayer led to a significant increase of the surface pressure only for lipid films consisting of a mixture of a negatively charged lipid with a high proportion of diacylglycerol. These alpha-actinin-containing films were transferred onto silanized quartz slides. Photobleaching experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…In addition, the I band shrunk (0.13 μm) and the A band was enlarged (1.57 μm) compared with live fish muscle ( P < 0.05), which indicated that the cytoskeletal connections between the myofibrils had been altered already (Papa and others ). According to previous studies, the damage of I bands and the segmentation of myofibrils resulted from the delocalization of α‐actinin (Fritz and others , Saad ). Compared with live muscle, there existed a clear Z line but a fainter M line and a thinner I band (0.27 μm) for fillets at –3 °C (Figure (C)), which underwent less change than fillets at 4 °C.…”
Section: Resultsmentioning
confidence: 87%
“…In addition, the I band shrunk (0.13 μm) and the A band was enlarged (1.57 μm) compared with live fish muscle ( P < 0.05), which indicated that the cytoskeletal connections between the myofibrils had been altered already (Papa and others ). According to previous studies, the damage of I bands and the segmentation of myofibrils resulted from the delocalization of α‐actinin (Fritz and others , Saad ). Compared with live muscle, there existed a clear Z line but a fainter M line and a thinner I band (0.27 μm) for fillets at –3 °C (Figure (C)), which underwent less change than fillets at 4 °C.…”
Section: Resultsmentioning
confidence: 87%
“…In contrast to the MLVs containing negatively charged DMPG, none of the charge isomers had a significant effect on the absorbance of neutral DMPC MLVs at 23°C (Table I). Because the inclusion of diacylglycerol has been reported to increase the interaction of some proteins with lipid despite its lack of charged groups (Soulages et al, 1995;Arnold et al, 1997;Fritz et al, 1993), the effect of MBP isomers on MLVs of DMPC/DAG 95:5 (m/m) and DMPC/DMPG/DAG (75: 20:5) was determined. The inclusion of DAG in either neutral DMPC or negatively charged DMPC/DMPG MLVs had no significant effect on the aggregation caused by any of the charge isomers (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…Typical examples are biomolecular recognition (1), cytoskeleton-membrane coupling (2,3), and interfacial activity of membrane-associated enzymes such as phospholipases (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%